GENOTOXIC EFFECT ON HEMATOLOGICAL AND MICRONUCLEUS ALTERATION OF COMMON CARP (Cyprinus carpio L.) EXPOSED BY GLYPHOSATE-BASED HERBICIDE - R Adharyan Islamy; Abdul Rahem Faqih; Yuni Kilawati; Yunita Maimunah; Mohamad Fadjar; Veryl Hasan; Wahyu Isroni; Novalina Serdiati; Ayu Winna Ramadhani; Diana Aisyah (Universitas Muhammadiyah Gresik, 2023)
Study aims to analyze the genotoxic potential of glyphosate-based herbicide on common carp (Cyprinus carpio L) using Micronucleus and hematological assay. The concentration of Glyphosate-based herbicide in this study was 0 ppm, 1.35 ppm, 1.8 ppm, 2.4 ppm, 3.2 ppm, 4.2 ppm, 6.5 ppm, and 8.7 ppm. Administration of herbicide base on modification of published methods with 96 hours of exposure. This research result has shown that the average number of micronuclei was increased simultaneously with increasing the concentration of herbicide exposure. There are also other types of cell nucleus abnormalities, namely: blebbed, lobed, notched, and binuclear. In the treatment of 0 ppm of herbicide shown blebbed nuclei are 8 ‰, lobed nuclei are 6.6 ‰, notched nuclei are 10 ‰, binuclei is 4 ‰. From the research results, it can be concluded that the LC50-96 hours exposure of the herbicide isopropylamine glyphosate in carp (Cyprinus carpio L.) was obtained at a concentration of 8.57 ppm. Based on the evaluation on hematology, it was found that there was a decrease in the number of erythrocytes, hematocrit, and hemoglobin of fish blood, whereas the number of leukocytes, micronuclei, and other abnormal micronuclei showed an increase along with the increase in the dose of exposure to the herbicide isopropylamine glyphosate, which indicates a genotoxic effect.